2022
DOI: 10.26714/jkj.10.2.2022.345-354
|View full text |Cite
|
Sign up to set email alerts
|

Tingkat Stres Kerja dengan Kinerja Perawat di Rumah Sakit: Literature Riview

Abstract: Penelitian ini bertujuan untuk menganalisis dan mengkaji hubungan antara tingkat stres kerja dengan kinerja perawat di poliklinik jiwa. Metode yang digunakan adalah literature review yaitu memerikksa literature ilmiah tentang suatu topic secara kritis. Artikel yang digunakan yang berhubungan dengan stres kerja dan kinerja perawat dan artikel tahun 2015-2020 menggunakan Google Schoolar dan Sematic Scholar. Dari 720 artikel, hanya 6  yang memenuhi kriteria inklusi. Berdasarkan hasil review, empat dari enam artik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Another factor that can negatively affect nurse performance is the workload experienced by nurses. Research by Mazelda, Arneliwati, and Erika (2022) and research by Ningsi, Jafiriati, & Muchtar (2022) found that there was a significant relationship between workload and nurse performance in hospitals. Workload measurement must also be carried out to identify performance problems that have not been optimal.…”
Section: Bivariate Analysismentioning
confidence: 99%
“…Another factor that can negatively affect nurse performance is the workload experienced by nurses. Research by Mazelda, Arneliwati, and Erika (2022) and research by Ningsi, Jafiriati, & Muchtar (2022) found that there was a significant relationship between workload and nurse performance in hospitals. Workload measurement must also be carried out to identify performance problems that have not been optimal.…”
Section: Bivariate Analysismentioning
confidence: 99%
“…Kesejahteraan spritual adalah pemahaman individual tentang dirinya, sosial, lingkungan dan Pencipta yang saling berkaitan sehingga terwujudnya suatu keharmonisan (Sriyanti et al, 2016). Dalam dunia keperawatan unsur spiritual merupakan praktik yang membantu pasien menghadapi masalah (stres) dan pemulihan (Dias, 2020). Aspek spiritual merupakan unsur integral karena memiliki efek relaksasi, meningkatkan endorphine, menetralisir stres serta meningkatkan sistem imun (Yanti et al, 2021).…”
Section: Pendahuluanunclassified